Culturally embedded resilience in the diabetes-COVID-19 syndemic: A phenomenological study of older adults in Bali, Indonesia - Putu Wira Kusuma Putra; Ni Komang Matalia Gandari; Ni Nyoman Suardani; Meriana Barreto Amaral (Nursing and Health Sciences Journal (NHSJ), 2026)
The COVID-19–diabetes mellitus (DM) syndemic disproportionately threatened older adults with Type 2 DM globally. This study investigates the culturally embedded resilience mechanisms enabling older Balinese adults with long-standing T2DM to maintain complication-free status during this crisis, directly challenging dominant deficit narratives. A descriptive phenomenological study grounded in Husserlian principles recruited ten older adults (aged 56–70; T2DM ≥20 years) in Badung Regency, Bali, utilizing purposive sampling. Bilingual researchers conducted in-depth interviews in participants’ preferred languages. Data were analyzed employing Colaizzi’s seven-step method, with methodological rigor ensured through reflexive bracketing and biweekly peer debriefing. Analysis revealed four interconnected themes illustrating a trajectory from psychological distress to disciplined self-management: (1) spiritually mediated acceptance of syndemic threat; (2) dietary management integrating biomedical guidance with traditional Balinese Usada practices; (3) adapted physical activity with strict pandemic protocol adherence; and (4) consistent biomedical treatment compliance. The Tri Hita Karana (THK) philosophy underpinned all themes, functioning as a cohesive cultural framework that seamlessly integrated psychological, behavioral, and biomedical domains into a unified self-management ecosystem. Resilience within this syndemic context emerged as a dynamic, culturally embedded process rather than a fixed individual trait. Healthcare systems must prioritize THK-informed, strength-based nursing programs as proactive resilience infrastructure, systematically integrating indigenous health philosophies into chronic disease management strategies for future global health emergencies.